The Three Cs of Administrative Office Management: Conceptions, Challenges, and Coping Mechanisms - Christopher D. C. Fancisco (International Journal of Case Studies in Business, IT and Education (IJCSBE), 2020)
The main aim of the study was to investigate different conceptions, challenges, and coping mechanisms with regards to administrative office management. To achieve this aim, the researcher selected three administrative officers within the Schools Division of City of Malolos, Bulacan during the school year 2019-2020. The study utilized a qualitative research design which aimed to describe the lived experiences of individuals in a certain phenomenon or human condition. Using transcriptions, codes, and triangulations of the data gathered, themes were extracted in the data analysis. Findings revealed that: (1) AOM was conceived as management of various documents for smooth transactions between teachers and school administrators, (2) AOM challenges were noted as encountering naughty teachers, unreturned office supplies, noisy location of the office facility and the office which is sometimes turned out to be a storage room, and (3) As AOM coping mechanisms, the respondents keep their strict mood and maintain a happy atmosphere to obtain a less stressed and a peaceful workplace. Conclusions were drawn and recommendations were offered.